2011
DOI: 10.1177/0961203311422709
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor geneBsmIpolymorphism B allele, but not BB genotype, is associated with systemic lupus erythematosus in a Han Chinese population

Abstract: The vitamin D receptor (VDR) gene is a candidate gene for susceptibility to autoimmune disorders. Association studies of VDR polymorphisms and risk of systemic lupus erythematosus (SLE) have often produced conflicting results in different ethnic backgrounds. The aim of this study is to test the association between VDR gene BsmI polymorphism and the genetic susceptibility to SLE in a Han Chinese population. Three hundred and thirty-seven patients with SLE and 239 healthy controls were genotyped for the VDR gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 29 publications
1
47
2
1
Order By: Relevance
“…The BsmI SNP may be associated with the different length polyadenylate sequence within the 3¢-untranslated region of the VDR gene (Uitterlinden et al, 2004). Recently, studies conducted by Luo et al (2012) have indicated that the level of VDR mRNA was remarkably reduced in patients with the VDR BsmI A (B) allele versus individuals bearing the GG (bb) genotype (Luo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BsmI SNP may be associated with the different length polyadenylate sequence within the 3¢-untranslated region of the VDR gene (Uitterlinden et al, 2004). Recently, studies conducted by Luo et al (2012) have indicated that the level of VDR mRNA was remarkably reduced in patients with the VDR BsmI A (B) allele versus individuals bearing the GG (bb) genotype (Luo et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of BsmI and FokI SNPs on the VDR protein function have already been studied (Arai et al, 1997;Luo et al, 2012;Monticielo et al, 2012). The FokI SNP situated in exon 2 results in the formation of a second methionine start site that leads to the production of a shorter protein receptor (Arai et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The function of BsmI and FokI SNPs on the biological effects of VDR have been extensively studied (18,(32)(33)(34). The BsmI polymorphism may change the length of the polyadenylate sequence in VDR transcript (18 significantly reduced the mRNA expression levels of VDR in carriers of the A (B) allele, as compared with subjects carrying the GG (bb) genotype (32).…”
Section: Discussionmentioning
confidence: 99%
“…The BsmI polymorphism may change the length of the polyadenylate sequence in VDR transcript (18 significantly reduced the mRNA expression levels of VDR in carriers of the A (B) allele, as compared with subjects carrying the GG (bb) genotype (32). The FokI SNP gives rise to two protein forms: A long VDR, encoded by the minor allele form (ATG; f), which contains three additional amino acids, and a shorter form, encoded by (ACG; F) (33).…”
Section: Discussionmentioning
confidence: 99%
“…The possible role of BsmI and FokI polymorphisms on the action of VDR have been demonstrated elsewhere (8,(49)(50)(51). The BsmI SNP may alter the length of the polyadenylate sequence within the 3'-untranslated region of the VDR gene (8).…”
Section: Discussionmentioning
confidence: 99%